P141 Differential expression of conventional and inhibitory VEGFA isoforms in normal and fibrotic fibroblasts–a potential role in IPF pathogenesis?. (14th November 2013) - Barratt, SL; Blythe, T; Jarrett, C; Ourradi, K; Maher, T; Welsh, GI; Bates, DO; Millar, AB
Abstract : Introduction: Vascular endothelial growth factor (VEGFA) has been implicated in the pathogenesis of Idiopathic Pulmonary Fibrosis (IPF). Two families of endogenous isoforms exist formed by alternative splicing of mRNA transcripts: the conventional potent angiogenic and mitogenic isoforms (VEGFxxx a family) and the VEGFxxx b family that is thought to have contrasting inhibitory functions. Hypothesis: We hypothesise that differential expression of VEGFxxx a and VEGFxxx b isoforms by fibroblasts may influence the development of IPF. Methods: Normal (NF) and fibrotic fibroblasts (FF) (from patients with proven UIP) were extracted from lung samples using the explant method. The expression of VEGFxxx a and VEGFxxx b by NF and FF was analysed at the mRNA level by RT-PCR and quantified by qPCR. Protein expression was determined by western blotting (WB) and ELISA. We sought to establish a potential functional effect of recombinant VEGF165 a and VEGF165 b proteins on fibroblasts by assessing the expression of a) the extracellular matrix (ECM) protein fibronectin and b) α-SMA, a marker of myofibroblast differentiation. Results: Both NF and FF expressed VEGFxxx a and VEGFxxx b isoforms at the mRNA level as determined by RT-PCR with confirmation by direct sequencing. There was no statistical difference in total VEGF mRNA expression between the two cell types by qPCR (p = 0.9307, NF n = 5, FF n = 6), but FF expressed significantly more VEGF165 b mRNA than NF (p = 0.05, NF n = 5, FF n = 6). Total VEGF protein expression was significantly increased in FF (mean expression NF = 180.5pg/ml vs FF 332.0pg/ml, p = 0.0012) by ELISA and confirmed by WB. Furthermore, increased VEGF165 b protein expression was also observed in FF by WB. Recombinant VEGF165 b had no effect on fibronectin or α-SMA expression in NF, but VEGF165 a (10ng/µl) significantly increased expression of fibronectin (p < 0.05). Interestingly, co-administration of VEGF165 a with VEGF165 b inhibited both α-SMA and fibronectin expression in these cells (Figure 1 ). Conclusion: Differential expression of VEGF isoforms between NF and FF suggests a potential role in the development of IPF. Furthermore, results suggest that factors altering the balance of splice variants may influence the surrounding fibrotic milieu.